Crosstalk between Tumor Cells and Macrophages in Stroma Renders Tumor Cells as the Primary Source of MCP-1/CCL2 in Lewis Lung Carcinoma - Yoshimura, Teizo; Liu, Mingyong; Chen, Xin; Li, Liangzhu; Wang, Ji Ming (Frontiers in Immunology, 2015)
The chemokine MCP-1/CCL2 is produced by a variety of tumors and plays an important role in cancer progression. We and others previously demonstrated that the primary source of MCP-1 in several mouse tumors, including 4T1 breast cancer, M5076 sarcoma and B16 melanoma, was stromal cells. In the present study, we identified that tumor cells were the primary source of MCP-1 in Lewis lung carcinoma (LLC), because MCP-1 mRNA was highly expressed in tumors grown in both WT and MCP-1-/- mice with elevated serum MCP-1 levels. Since LLC cells isolated from tumors expressed low levels of MCP-1 in vitro, it appeared that the tumor-stromal cell interaction in a tumor microenvironment increased MCP-1 expression in LLC cells. In fact, co-culture of LLC cells with normal mouse peritoneal macrophages or normal lung cells containing macrophages increased MCP-1 expression by LLC cells. Macrophages from TNFα-/- mice failed to activate LLC cells and anti-TNFα neutralizing antibody abolished the effect of WT macrophages on LLC cells. When LLC cells were transplanted into TNFα-/- mice, the levels of MCP-1 mRNA in tumors and serum MCP-1 levels were markedly lower as compared to WT mice, and importantly tumors grew more slowly. Taken together, our results indicate that TNFα released by tumor cell-activated macrophages is critical for increased MCP-1 production by tumors cells. Thus, disruption of tumor-stromal cell interaction may inhibit tumor progression by reducing the production of tumor-promoting proinflammatory mediators, such as MCP-1.